Conserved and unique features of the fission yeast core Atg1 complex. Issue 12 (2nd December 2017) - Nanji, Tamiza; Liu, Xu; Chew, Leon H.; Li, Franco K.; Biswas, Maitree; Yu, Zhong-Qiu; Lu, Shan; Dong, Meng-Qiu; Du, Li-Lin; Klionsky, Daniel J.; Yip, Calvin K.
ABSTRACT: Although the human ULK complex mediates phagophore initiation similar to the budding yeast Saccharomyces cerevisiae Atg1 complex, this complex contains ATG101 but not Atg29 and Atg31. Here, we analyzed the fission yeast Schizosaccharomyces pombe Atg1 complex, which has a subunit composition that resembles the human ULK complex. Our pairwise coprecipitation experiments showed that while the interactions between Atg1, Atg13, and Atg17 are conserved, Atg101 does not bind Atg17. Instead, Atg101 interacts with the HORMA domain of Atg13 and this enhances the stability of both proteins. We also found that S. pombe Atg17, the putative scaffold subunit, adopts a rod-shaped structure with no discernible curvature. Interestingly, S. pombe Atg17 binds S. cerevisiae Atg13, Atg29, and Atg31 in vitro, but it cannot complement the function of S. cerevisiae Atg17 in vivo. Furthermore, S. pombe Atg101 cannot substitute for the function of S. cerevisiae Atg29 and Atg31 in vivo. Collectively, our work generates new insights into the subunit organization and structural properties of an Atg101-containing Atg1/ULK complex.